2019
DOI: 10.1111/ics.12588
|View full text |Cite
|
Sign up to set email alerts
|

NLRP inflammasomes and induced skin inflammation, barrier recovery and extended skin hydration

Abstract: OBJECTIVE: In vitro assays were designed to examine the release of active Caspase-1 (ACasp-1) from NLRP inflammasome-activated Normal Human Epidermal Keratinocytes (NHEK) employing a bioluminescent assay specific for measuring inflammasome-induced Correspondence: James V. Gruber, BotanicalsPlus â ,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Gruber et al suggested that the three ingredients blend and can affect in vitro inflammaging by modulating the expression of active Caspase-1 in inflammasome-activated NHEK, which are key to the process of inflammaging by triggering the release of reservoirs of IL-1 and IL-18, leading later to a release of T cells and dendritic immune response cells. The authors pointed out that these results need to be confirmed by long-term studies [25]. Vollono et al's article reviewing several studies, showed that a potential anti-inflammatory and anti-oxidant effect could be achieved by topical use of curcumin, which may be due to its ability to reduce levels of TNF-α by activated macrophages, inhibit phosphorylase kinase, reduce the number of IL-17A, IL-17F, IL-22 and other pro-inflammatory cytokines, a high level of which has been observed in diseases with underlying inflammaging processes [8].…”
Section: Factors That Inhibit Inflammagingmentioning
confidence: 98%
See 1 more Smart Citation
“…Gruber et al suggested that the three ingredients blend and can affect in vitro inflammaging by modulating the expression of active Caspase-1 in inflammasome-activated NHEK, which are key to the process of inflammaging by triggering the release of reservoirs of IL-1 and IL-18, leading later to a release of T cells and dendritic immune response cells. The authors pointed out that these results need to be confirmed by long-term studies [25]. Vollono et al's article reviewing several studies, showed that a potential anti-inflammatory and anti-oxidant effect could be achieved by topical use of curcumin, which may be due to its ability to reduce levels of TNF-α by activated macrophages, inhibit phosphorylase kinase, reduce the number of IL-17A, IL-17F, IL-22 and other pro-inflammatory cytokines, a high level of which has been observed in diseases with underlying inflammaging processes [8].…”
Section: Factors That Inhibit Inflammagingmentioning
confidence: 98%
“…oligomeric α-Synuclein [28] UV radiation [9][10][11][12][13]19,27,29] PM [10,11,21,23] ROS/oxidative stress [10][11][12][13]15,21,27] tobacco extract [11,21] excessive nutrient supply [12] living in urban areas [21] three ingredient blends (probably only in vitro, need more long-term studies) [25] bakuchiol and vanilla tahitensis extract [30] curcumin [8,21] aloe vera topically [21] resveratrol [21] AdipoRon [22] topical nanoemulsion formulation containing tocotrienol-rich fraction [9] Centella asiatica extract [26] estrogen [24] rapamycin topically (potentially) [10] (in [14] no beneficial effects) metformin topically [10,14] emollients/moisturizers (preventing epidermal disruption) [16] seaweed extract (Laminaria Japonica) [17] microbiota (i.e., skin, gut) [6,[13][14][15] epidermal function (dysfunction pro-inflammaging, normal function anti-inflammaging)…”
Section: Factors Accelerating Inflammaging Factors Slowing Down Infla...mentioning
confidence: 99%
“…20 In addition, the studies examine the impact of PQQ2Na on the control of NLRP-induced active Caspase-1 release in UVB and ATP-activated NHEKs using previously reported testing procedures. 17,21,22 Like mitochondrial biogenesis, the NLRP-induced inflammasome activation of active Caspase-1 is intimately related to the mitochondrial ROS activity. 23…”
Section: Introductionmentioning
confidence: 99%
“…CBD Isolate typically has a Cannabidiol purity of greater than 99% with no residual Tetrahydrocannabinol (THC). Recently, a model for examining NLRP inflammasome‐activated release of active caspase‐1 in UVB and ATP‐activated Normal Human Epidermal Keratinocytes (NHEK) was reported [12–14]. This model allows for direct examination of the impact of topical treatments on activated NHEKs through measurement of release of active caspase‐1 (ACasp‐1).…”
Section: Introductionmentioning
confidence: 99%